Electron Drift Resonance in the MHD‐Coupled Comprehensive Inner Magnetosphere‐Ionosphere Model. Issue 12 (7th December 2017) - Komar, C. M.; Glocer, A.; Hartinger, M. D.; Murphy, K. R.; Fok, M.‐C.; Kang, S.‐B.
Abstract: Relativistic electrons in the outer radiation belt are highly dynamic and respond to interplanetary solar wind structures interacting with the Earth's magnetic field. A known mechanism dictating electron dynamics is the drift‐resonant interaction with ultralow frequency (ULF) waves. The present work simulates the ring current and radiation belt electron populations in the bounce‐averaged, kinetic Comprehensive Inner Magnetosphere‐Ionosphere model coupled with the Block Adaptive Tree Solar Wind Roe‐type Upwind Scheme global magnetospheric magnetohydrodynamic (MHD) code using an idealized ULF wave solar wind density driver. ULF waves generated with 10 min periods (at 1.67 mHz frequencies) in the MHD model are characterized and the corresponding energization of electrons and radial transport of electron phase space density is presented. The drift‐resonant electron energy is determined in the simulation and is consistent with the electron resonance conditions in dipolar magnetic fields. The present results will be an important component of understanding inner magnetospheric dynamics and how these inner magnetospheric populations interact with ULF waves resulting from interplanetary solar wind structures. Key Points: Electron drift‐resonant interaction captured in kinetic inner magnetosphere model coupled to global magnetohydrodynamic magnetospheric code Dynamic pressure fluctuations drive ultralow frequency waves; radiation belt electrons are energized and transported via drift resonance Electrons interact with modeled ultralow frequency waves; electron interaction is characterized as a function of radial distance and energy